Improving Cash Flow Management - Abbasov, S. (Економічний вісник Донбасу, 2021)
The article discusses various scientific and theoretical views of famous economists on the essence, purpose and objectives of cash flow as an object of financial management and makes appropriate conclusions. Cash flow has a unique property of financial liquidity and fully implements the economic functions that relate to it. Cash flow management is a financial tool that allows you to achieve high final results of the financial and economic activities of the company, that is, maximize profits. The principles, methods and a comprehensive analysis of cash flow management are considered. The stages of the cash flow management process and their information support are described in detail. The principles and stages of creating an organizational and functional cash flow management mechanism were considered and emphasized that the formation of an excellent cash flow management mechanism will allow the company to attract additional investments to carry out its current activities and enter foreign markets, including the stock market. Issues of disclosing shadow cash flows in financial management and determining its role in increasing the value of the company and the risks associated with macroeconomic regulation have been studied in detail. There are reasonable suggestions and recommendations for improving the cash flow management mechanism.